Angiotensin 1 Converting Enzyme Encoding Gene Polymorphism in Renal Patients - Sajid Ali, Muhammad Tariq Mehr, Muhammad Bilal, Muhammad Zubair, Ahmad Shamim Khan, Noreen Mehmood (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Angiotensin I is converted to angiotensin II by an angiotensin-converting enzyme, which is an important component of renin-angiotensin framework. Multifactorial chronic kidney disease includes risk factors such as hypertension, obesity, inherited factors, and diabetes. A genetic factor associated with premature signs of renal failure is predominantly increased arterial hypertension and albumin excretion, which add to the pathophysiological movement of disintegration in renal capacity. This enzymatic assay aimed to detect ACE levels in various renal patients compared with controls to confirm the relationship between ACE quality polymorphism and enzymatic ACE levels. Materials and Methods: The study population of our study included 56 patients with chronic kidney disease. Who was confirmed to have chronic kidney disease after being diagnosed in the dialysis ward of the tertiary care hospital. Results: A total of 56 chronic kidney disease were enrolled. Mean age of patients were 55.1±13.6. Among total recruited patients, 60% male patients and 40% were female patients. The HDL, and LDL were lower in chronic kidney disease patients than control group. While BMI, total cholestrol, triglyceride, systolic blood pressure, diastolic blood pressure, and ACE level were found higher in CKD patients than control group. The frequency of genotypes ACE II, ID, and DD in patients groups was 12 (12.43%), 28 (48.21%), and 17 (30.35%). Conclusion: Our study result indicates that the D allele is involved in the progression of chronic diseases. When we look at the frequency of I and D alleles it clearly shows that the frequency of the D allele is significantly higher in patients with CKD than the frequency of the I allele. Keywords: ACE, CKD, Renal patients, Polymorphism